KINERJA BADAN PELAYANAN PERIZINAN TERPADU DAN PENANAMAN MODAL (BPPTPM) DALAM PELAYANAN PEMBUATAN SURAT IZIN USAHA PERDAGANGAN (SIUP) DI KOTA BENGKULU - Saputra, Edo (Jurnal Governance dan Administrasi Publik, 2020)
The aims of this research to determine whether the performance of the agency as an integrated licensing services and investment in  he service of making the trading license from the aspect of productivity, quality of service, responsiveness, responsibility, and accountability in Kota Bengkulu. This research uses a descriptive qualitative research and data collection was done by observation, interview and documentation. Informants were 11 people consisting of employees of an integrated licensing services and investment (BPPTPM) Kota Bengkulu with 9 people and communities on permits with three people. The result showed the problem, that is: 1)In the process of regristration, one of wich is a letter of permission HO early and therefore had to wait for the process of making HO firstly.2) The process of making the trading license must be wait for a recommendation from the relevant agencies, the official trade Kota Bengkulu. If no letter of recommendation that the process has not been carried. 3) The distance between the relevant agencies with offices BPPTPM far that takes time and costs where is a budget for accommodation is not infringed by BPPTPM Kota Bengkulu.